VASYL STEFANYK AND THE MANIFESTOS OF «YOUNG POLAND» - Yamborko, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article researches on the creative interrelations between Vasyl Stefanyk and the representatives of the modernistic literary grouping «Young Poland». It proves influences of the latter over the expressionism of the Ukrainian author of novellas and defines the rootage of his belletristic works into the traditions of the Ukrainian belletristic prose of the turn of the before last centuries. It concretises the notion “Krakow as Text” in the life and creations of the classic of the Ukrainian literature.